2006
DOI: 10.1128/aac.50.4.1411-1418.2006
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Chromosome-Encoded Microcins

Abstract: Microcins are ribosomally synthesized peptide antibiotics that are produced by enterobacterial strains. Although the first studies concentrated on plasmid-encoded activities, in the last years three chromosomeencoded microcins have been described: H47, E492, and M. Here, a new microcin, I47, is presented as a fourth member of this group. Common features exhibited by chromosome-encoded microcins were searched for. The comparison of the genetic clusters responsible for microcin production revealed a preserved ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 26 publications
2
55
0
Order By: Relevance
“…Previous reports have shown that these genes are often located on the same pathogenicity island (PAI) (12,16,19), and this would also explain our data. In addition, PAI-CFT073-serX contains the microcin M/H47 gene cluster, F1C fimbrial genes, and the iro gene cluster (4).…”
Section: Figsupporting
confidence: 77%
“…Previous reports have shown that these genes are often located on the same pathogenicity island (PAI) (12,16,19), and this would also explain our data. In addition, PAI-CFT073-serX contains the microcin M/H47 gene cluster, F1C fimbrial genes, and the iro gene cluster (4).…”
Section: Figsupporting
confidence: 77%
“…In addition to enterobactin synthesis, the modification requires genes of the iroA cluster for salmochelin synthesis, essentially iroB and iroD for glucosylation and backbone linearization, respectively. A similar posttranslational processing is anticipated for MccI47 and MccM (244,252). The modified microcins are recognized and taken up by the catecholate siderophore receptors FepA, Cir, and Fiu of E. coli and FepA, Cir, and IroN of S. enterica in a cooperative and TonB-dependent manner (77,244).…”
Section: "Trojan Horse" Antibioticsmentioning
confidence: 94%
“…Microcins have a broad spectrum of bactericidal activity against Enterobacteriaceae, including Escherichia, Salmonella, Shigella, Citrobacter, Klebsiella, and Enterobacter (28,30). The synthesis of MccH47 is encoded by mchB within an ϳ10.5-kb mch47 operon (GenBank accession number AJ009631) (33). The mch47 peptide is synthesized as a 75-residue precursor that is processed during secretion to a 60-residue mature extracellular peptide of 4.9 kDa (36).…”
mentioning
confidence: 99%